Rapidly Progressive Paraplegia Resulting from Latent Cervical Dural Arteriovenous Fistula After Lumbar Surgery: A Case Report. Issue 1 (January 2022) - Han, Zhenchuan; Ren, Bowen; Liu, Yang; Liu, Jianheng; Wang, Zheng; Mao, Keya
Abstract : Case: A 68-year-old woman developed symptoms of acute paraplegia due to an occult cervical dural arteriovenous fistula (DAVF) after a minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). She was subsequently diagnosed by angiography and treated with vascular embolization. A 2-year follow-up showed that the patient's upper limb muscle strength returned to normal, and the lower limb muscle strength partially improved with remnant motor dysfunction. Conclusion: For patients with symptoms of nerve injury inconsistent with the spinal surgery site, a possibility of DAVF should be considered, and related investigations should be performed. Once diagnosed, active treatment is required.